Synergy in Governance and Traffic Asset Management of the Ponorogo Transportation Agency: Bridging the Public Service Performance Gap - M. Rama Kukuh Prayoga; Fedianty Augustinah; Priyanto Priyanto (International Journal of Social Science and Humanity, 2025)
This qualitative study examines the Public Service Performance Gap at the Ponorogo Regency Transportation Agency (Dishub) in managing high-risk traffic assets, which stems from the failure to synergise Normative Governance with operational Public Asset Management (MAP). Utilising Edwards III's Policy Implementation Model and GG/NPS principles, the core finding indicates that synergy failure is mediated by a Reactive Bureaucratic Disposition. While Dishub adheres procedurally, asset maintenance is largely reactive—performed only after damage or public complaint—not preventive. This non-responsive attitude limits accountability to reporting outputs disconnected from physical service outcomes, leading to low service quality. The proposed substantive solution is to activate Community Involvement (NPS) as a key moderator, which is currently weak, by integrating Functional Participation into the agile MAP cycle. The research recommends an e-governance system with KPIs, where transparently integrated citizen reports automatically trigger work orders, creating external public accountability pressure that forces the reactive bureaucracy to act proactively.